Development of Storytelling-based Learning in Stimulating Children's Receptive and Expressive Language - Sadaruddin, Sadaruddin; Cahaya, Cahaya; Syamsuardi, Syamsuardi; Musi, Muhammad Akil; Sarimanah, Eri (Program Studi Magister Pendidikan Anak Usia Dini, 2025)
This study aims to develop an innovative and effective storytelling learning method to stimulate receptive and expressive language skills in early childhood. The main issue faced at Doa Ibu Early Childhood Education Kindergarten, Makassar is the low receptive and expressive language abilities of the children. The study uses a qualitative approach with the Lesson Study method, implemented over two cycles, involving 15 children. Data were collected through observation, interviews, and documentation. Data analysis was conducted using descriptive methods and the calculation of descriptive statistics with N Gain to assess the effectiveness of the learning. In the first cycle, audio-visual media was used in storytelling learning but was not effective in capturing the children's attention until the end of the story. The second cycle introduced an interactive approach by combining video visuals and hand puppets, which increased participation and active learning. The results of the study show that the combination of video-visual media and hand puppets in three learning steps— tonton cerita (watch the story), ulas cerita (review the story), and ekspresikan cerita (express the story)—abbreviated as TRUE Storytelling, proved to be an effective method for enhancing children's receptive and expressive language abilities